Why SMEs comply: an empirical investigation of tax knowledge, trust, system perception and penalties in the self-assessment environment in Malaysia - Ahmad Sabri, Siti Madihah; Abdul Rasit, Zarinah; Abd Hamid, Nadiah; Ismail Khan, Norziaton; Tajul Urus, Sharina (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2025)
Tax non-compliance remains a persistent challenge for tax authorities to promote voluntary tax compliance, particularly among Small and Mediumsized Enterprises (SMEs) in developing economies. Key concerns include limited tax knowledge, weak trust in the Inland Revenue Board of Malaysia (IRBM), perceptions of the tax system, and the effectiveness of tax penalties. This study aimed to examine the determinants of voluntary tax compliance among Malaysian SMEs operating under the Self-Assessment System (SAS). Drawing on the Theory of Planned Behaviour, this research examined the influence of tax knowledge, trust in tax authorities, perceived fairness of the tax system, and perceived severity of tax penalties on compliance behaviour. Data were collected through a structured questionnaire distributed to SME owners and managers across the Klang Valley region, yielding 220 responses. The data were analysed using correlation and multiple regression analyses to test the hypothesised relationships. The results revealed that all four factors were statistically significant and positively influenced voluntary tax compliance. Tax knowledge, trust in the IRBM, perceptions of the tax system, and implementing effective penalties were key to enhancing compliance. The study contributes to the growing body of tax compliance literature by offering empirical evidence from the Malaysian SME context and provides practical insights for policymakers seeking to strengthen tax compliance.